ECOLOGICAL ETHICS AND ITS PHILOSOPHICAL FOUNDATIONS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Annotation. This scientific article examines environmental ethics as one of the most significant fields of contemporary philosophical thought aimed at understanding the harmonious interaction between humans and nature. The author analyzes the philosophical foundations of environmental ethics, including the categories of moral responsibility, value orientations, and ethical choice in the context of intensifying environmental and civilizational challenges. Special attention is given to the formation of environmental consciousness as a key factor in sustainable development and the transformation of social practices. The article also reveals the role of environmental ethics in rethinking an individual’s worldview, its influence on cultural norms, and the strategic goals of society. Thus, environmental ethics is presented as a fundamental basis for the philosophical understanding of humanity’s future, oriented toward harmony, sustainability, and moral maturity.
Keywords: environmental ethics, philosophy, morality, responsibility, environmental consciousness, sustainable development, civilization